PENGARUH IKLAN PADA MEDIA TELEVISI TERHADAP MINAT BELI (STUDI PADA CALON KONSUMEN BUKALAPAK.COM DI KOTA DENPASAR) - Winata, Ade; Nurcahya, I Ketut (E-Jurnal Manajemen; Vol 6 No 10 (2017), 2017)
The purpose of this study was to determine the effect of advertising (advertising messages, music, advertising, illustration of stories and commercials) Bukalapak.com on television media to prospective consumers buying interest Bukalapak.com in Denpasar. This research was conducted in the city of Denpasar. The size of the sample taken 90 respondents by method. Purposive sampling the data were collected by distributing a questionnaire using a scale Likert to measure 15 indicators. The analysis technique used is multiple linear regression analysis. The study found that the advertising message, advertising music, illustrated stories, and commercials positive and significant impact on consumer buying interest. Based on the results of the calculation of the coefficient of determination can be explained that the simultaneous influence of a variable message advertising, advertising music, illustrated stories and commercials on consumer buying interest. While the result in partial advertising messages, music advertising, illustration stories and commercials positive and significant impact on consumer buying interest.